The Effect of Intradialytic Exercise on Dialysis Efficacy, Serum Phosphate, Hemoglobin and Blood Pressure Control and Comparison between Two Exercise Programs in Hemodialysis Patients - Mohammad Javad Fallahi; Shahrzad Shahidi; Ziba Farajzadegan (مجله دانشکده پزشکی اصفهان, 2008)
Abstract There is some evidence that showed intradialytic exercise increases dialysis efficacy and removes phosphate. This study examined the impact of intrdialytic exercise on dialysis efficacy, serum phosphate, control of blood pressure and hemoglobin level. Background: In this clinical trial, 14 patient (47/13+/-14/6 years) on hemodialysis (6-180 months), after excluding contraindication, participated for eighth week exercise program in which they pedaled a bicycle at sub maximal workload. Total duration of exercise was one hour in the first two hours of HD. Patients divided into two groups: group A: two parts of 30 minutes exercise. Group B: six parts of 10 minutes exercise. Pre- dialysis blood pressure, URR (urea reduction ratio), sp Kt/V, serum phosphate, calcium and hemoglobin were measured initially, at the end of 4th week and 8th week of study. Methods: Two patients discontinued the study. sp Kt/V despite 20% increase at the end of study was not significant. Mean systolic blood pressure decreased 5.4 mmhg that was significant (Pv: 015). There is no significant difference between two groups except in the dose of phosphate binder at the end of first month and the end of study. Findings: One hour intradialytic exercise can cause significant reduction in systolic blood pressure. Clinical increase in sp Kt/V and slijht reduction in serum phosphate and hemoglobin level. Two part time of 30 minutes exercise program was more effective to lower the dose of phosphate binder drug. But comprehensive studies are needed to established definite benefits of intradialytic exercise and relative advantages of different exercise programs. Conclusion: Exercise, hemodialysis, dialysis efficacy. Key words: